THE REFLECTIONS OF CONCEPTUAL FRAMEWORK OF FINANCIAL REPORTING ISSUED BY THE INTERNATIONAL ACCOUNTING STANDARDS BOARD (IASB) IN THE ACCOUNTING PRACTICE ENVIRONMENT - A CRITICAL THEORETICAL STUDY - Saeed, Nawzad; Musto, Narin (Humanities Journal of University of Zakho, 2024)
This study aims to identify the major changes in the conceptual framework for financial reporting issued by the International Accounting Standards Board (IASB) in 2018 and their positive and negative impact on the accounting practice environment. The study is conducted within a philosophical framework that includes a review and analysis of previous studies related to this relationship. The study used the critical descriptive approach by reviewing references, research and studies related to the study, and analyzing different points of view on the fundamental changes in the new conceptual framework. The researchers concluded from their analysis of these studies that the new conceptual framework and its updates played a fundamental role in directing accounting practices in the right direction and choosing unified accounting treatments in different environments. They also helped in finding appropriate measurement alternatives that are compatible with the changes and fluctuations facing business applications. This has improved and enhanced the quality of financial statement content. In their analysis, the researchers determined that the new conceptual framework does not encompass several areas within the accounting practice enviroment. In addition, guidance in some areas of the framework is unclear, particularly those areas relating to measurement, presentation, and recognition principles and accounting policies. This poses a challenge to issuing efficient and effective standards. The researchers recommend that the proposed changes to the conceptual framework for financial reporting be evaluated by professional bodies and preparers of financial statements to keep pace with the changes occurring in the accounting practice environment.